The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1140/epje/i2017-11587-3
|View full text |Cite
|
Sign up to set email alerts
|

Image windowing mitigates edge effects in Differential Dynamic Microscopy

Abstract: Differential Dynamic Microscopy (DDM) analyzes traditional real-space microscope images to extract information on sample dynamics in a way akin to light scattering, by decomposing each image in a sequence into Fourier modes, and evaluating their time correlation properties. DDM has been applied in a number of soft-matter and colloidal systems. However, objects observed to move out of the microscope's captured field of view, intersecting the edges of the acquired images, can introduce spurious but significant e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…Note that the scattering functions are shown for a q-value of 4.65 mm À1 , which is an intermediate value where the ISF is not affected by noise or by drifting of the particles out of the field of view (see ref. 52 and ESI, † Fig. S3).…”
Section: Effect Of Crosslinking On Particle Diffusivity In Hyaluronanmentioning
confidence: 99%
“…Note that the scattering functions are shown for a q-value of 4.65 mm À1 , which is an intermediate value where the ISF is not affected by noise or by drifting of the particles out of the field of view (see ref. 52 and ESI, † Fig. S3).…”
Section: Effect Of Crosslinking On Particle Diffusivity In Hyaluronanmentioning
confidence: 99%
“…While performing the numerical Fourier transform, care has to be taken to avoid imaged inhomogeneities leading to spectral leakage. 39 Assuming a stationary and isotropic signal, the signal statistics and hence the power spectrum are independent of time t and the direction of the scattering vector Q. To improve statistics, thus, a temporal average over t and an azimuthal average over the angle φ in the Q plane are performed and indicated by t,φ .…”
Section: Determination Of the Steady-shear Viscosity In A Ddm Experimentsmentioning
confidence: 99%
“…It has been recently shown that multiplying the images with a windowing function before performing the Fourier transform operation removes the artifacts due to the finite image size and improves the determination of D(q,t), especially for those q for which the signal is comparable or smaller than the noise [46]. We thus apply this algorithm in our analysis.…”
Section: E Differential Dynamic Microscopymentioning
confidence: 99%